Frontispiece: Iron‐Catalyzed Olefin Metathesis: Recent Theoretical and Experimental Advances. Issue 62 (7th November 2022) - Grau, Benedikt W.; Neuhauser, Alexander; Aghazada, Sadig; Meyer, Karsten; Tsogoeva, Svetlana B.
Abstract : Olefin metathesis gives access to important petrochemicals, polymers, and pharmaceuticals. The catalysts for these transformations are often based on high‐valent metal ions e.g., Ru(IV), which have been improved through ligand modifications. An attractive, but challenging goal is to catalyze olefin metathesis with a non‐toxic, bio‐compatible, and abundant element; namely, iron . Indeed, the first pieces of evidence suggest that low‐valent Fe(II) complexes are active in olefin metathesis. This Review by K. Meyer, S. B. Tsogoeva, et al. (DOI: 10.1002/chem.202201414 ) summarizes the key advances and challenges in this endeavor.